2018
DOI: 10.1590/1806-93042018000300003
|View full text |Cite
|
Sign up to set email alerts
|

The Baby-Friendly Hospital Initiative: increasing breastfeeding and decreasing infant mortality in Brazil

Abstract: Objectives: to estimate the population attributable fraction of preventable infant mortality rates due to changes in breastfeeding (BF) indicators attributable to the Baby Friendly Hospital Initiative (BFHI). Methods: an estimate on the impact of BFHI in reducing infant mortality with an inferential level of plausibility, using secondary data from the II Breastfeeding Prevalence Survey of 2008. Initially, the effect of BFHI on breastfeeding in the first hour of life, exclusive breastfeeding, and any breastfee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
7
1
2
Order By: Relevance
“…In this study, we found a high prevalence of complement offer, which corroborates the ndings of studies conducted in other countries and in Brazilian cities [2,14,15,19]. Although the WHO recommends skin-toskin contact at birth, breastfeeding in the rst hour of life and "Do not give the newborn baby any food or drink other than breast milk, unless such procedure has a medical indication", most NB received the complement in the rst hours and days after birth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we found a high prevalence of complement offer, which corroborates the ndings of studies conducted in other countries and in Brazilian cities [2,14,15,19]. Although the WHO recommends skin-toskin contact at birth, breastfeeding in the rst hour of life and "Do not give the newborn baby any food or drink other than breast milk, unless such procedure has a medical indication", most NB received the complement in the rst hours and days after birth.…”
Section: Discussionsupporting
confidence: 89%
“…Exclusive Breastfeeding (EB) -which should be offered from birth to the rst 6 months of life -is among the World Health Organization recommendations for reducing child mortality [1][2][3]. Studies show that the chances of remaining in breastfeeding (BF) in the rst month and in the following months are greater when the newborn (NB) is placed in immediate contact with the genitor, skin-to-skin, and even more when it is possible to accomplish the "Golden Hour".…”
Section: Introductionmentioning
confidence: 99%
“…The BF in the first 6 months of life of children born in BFHI hospital, had the effect of reducing deaths from any cause and infection. [3] In a neonatal network of 18 neonatal units in the United Kingdom with the "Getting It Right From the Start Programme" intervention, the rate of EBF and motherchild skin-to-skin method was increased and this associated with the decrease in costs due to gastroenteritis (GE) and necrotizing enterocolitis (NEC) in more than half a million pounds sterling, as demonstrated by a cost-benefit study. [4] The establishment of EBF is favorably influenced thanks to BFHI or related practices, even so, difficulties are seen in the application of some of its components, such is the case of prenatal education about EBF (step 3) and in support for postnatal EBF (step 10) associated with a shorter duration of EBF.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the BFHI was adopted as a public policy within the health system since 1992; yet the current coverage is only 23•4 % of births in BFHI facilities nationwide (7,11) , indicating the relevance of addressing the programme implementation challenges. A recent analysis conducted in Brazil indicated that BFHI is effective in reducing infant mortality by promoting breast-feeding (12) ; nevertheless, there is still a gap in the literature regarding the costs associated with adoption of BFHI (i.e., whether effects outweigh financial resources applied in its implementation and maintenance).…”
mentioning
confidence: 99%